An Analysis of Figurative Language in Short Story “The Happy Prince” by Oscar Wilde - Lidya Rona Mentari (Journal of English for Specific Purposes in Indonesia (JESPI), 2023)
This study analyzed the figurative language utilized in Oscar Wilde's short story "The Happy Prince." This study aims to identify the most common figure of speech by examining the figurative m language utilized in the short story "The Happy Prince." A descriptive qualitative methodology was used to analyse the figurative language in "The Happy Prince." This study's data source was the text of "The Happy Prince," a short story. The first step was to read "The Happy Prince," a short story. Second, seek for figurative language in "The Happy Prince," a short story. The third part discusses the many figurative language techniques used in "The Happy Prince” short story. Fourth, the utilization of figurative language in each sentence from the short story "The Happy Prince" was classified. Lastly, the data analysis was applied to produce the report or conclusion. Based on the analysis, the researcher found 25 data that contain figurative language. There is simile appears 10 times (40%), metaphor appears only 1 time (4%), personification appears 9 times (36%), synecdoche appears only 1 time (4%), symbol appears 2 times (8%), hyperbole/overstatement appears 2 times (8%). In this research, the simile is the dominant type of figurative language that found in “The Happy Prince” short story.